2008
DOI: 10.4238/vol7-1gmr403
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distance estimates among single cross hybrids and correlation with specific combining ability and yield in corn double cross hybrids

Abstract: ABStrACt. The objective of the present study was to correlate the genetic distances (GD) of single cross hybrids with yield, heterosis and specific combining ability (SCA) in the double cross hybrid synthesis. For this, 10 single cross commercial hybrids were used from different companies, and all the possible double hybrids were synthesized by a complete dialell. The hybrids were assessed in 15 locations in the 2005/2006 agricultural season, using the randomized complete block design with three repetitions. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 14 publications
1
20
1
2
Order By: Relevance
“…correlations were extremely low and non-significant (at 5% probability), making the use of RAPD markers unfeasible for agronomic conclusions such as the prediction of hybrid heterosis and establishment of heterotic groups. Our findings corroborate similar studies that used other types of DNA markers (Lee et al, 1989;Dudley et al, 1991;Balestre et al, 2008). Regarding RAPD markers, Rinaldi et al (2007) also did not infer a significant correlation between heterosis and productivity in Brazilian popcorn populations.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…correlations were extremely low and non-significant (at 5% probability), making the use of RAPD markers unfeasible for agronomic conclusions such as the prediction of hybrid heterosis and establishment of heterotic groups. Our findings corroborate similar studies that used other types of DNA markers (Lee et al, 1989;Dudley et al, 1991;Balestre et al, 2008). Regarding RAPD markers, Rinaldi et al (2007) also did not infer a significant correlation between heterosis and productivity in Brazilian popcorn populations.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, Lanza et al (1997) obtained a significant correlation between grain yield data and random amplified polymorphic DNA (RAPD)-based genetic distances. Besides, Balestre et al (2008), with the aim of correlating the genetic distance of single cross hybrids with yield, heterosis and specific combining ability (SCA) in the double cross hybrid synthesis, concluded that there was a moderate correlation between genetic distance and heterosis (r = 0.40) and genetic distance and SCA (r = 0.38), but the authors found that the molecular markers were efficient in placing hybrids in different heterotic groups and were also useful in eliminating the most negative heterosis and SCA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, some methodologies have been proposed for the prediction of untested crosses, i.e., the use of the genetic distance by molecular markers in the prediction of SCA and heterosis values (Melchinger, 1999;Reif et al, 2003;Balestre et al, 2008a). However, results have demonstrated little efficacy and repeatability (Dias et al, 2004).…”
Section: Introductionmentioning
confidence: 99%